Survey on hospital chaplains - Fasanella, Giuseppe; Sgreccia, Elio (Medicina e Morale, 1991)
This contribution consists in the final report on research on the hospital chaplains carried out in Italy under the initiative of the National Council for the Health Pastoral of the ltalian Episcopal Conference. After the description of the results which includes many tables, in the conclusion the authors discuss the validity of the survey and they present the various characterists of the chaplains and the type of pastoral which results from the analysis of the questionnaires.